Role of biofeedback in optimizing psychomotor performance in sports - Paul, M.; Garg, K.; Sandhu, J. S. (Asian Journal of Sports Medicine, 2012)
Purpose: Biofeedback is an emerging tool to acquire and facilitate physiological and psychological domains of the human body like response time and concentration. Thus, the present study aims at determining the reconstitution of psychomotor and performance skills in basketball players through biofeedback training.